Nanoflower-like PdCuP catalysts for enhancing ethanol electrooxidation - Wei, Longbo; Zhao, Liubin; Ye, Meiling; Zhu, Aimei; Zhang, Qiugen; Liu, Qinglin (International journal of hydrogen energy, 2025)
Direct ethanol fuel cells with the advantages of high safety, portability and energy conversion efficiency draw high attention and have great prospects for the future. However, their commercial application was limited by the low catalytic activity and anti-poisoning of the anodic catalyst. In this work, nanoflower-like PdCuP catalysts (PdCuP NFs) assembled by nanosheets was successfully prepared by wet chemical method, where W(CO)6 and CH3COOH were used as structure-oriented agents. Towards to ethanol oxidation reaction (EOR), the highest peak current density of as-prepared PdCuP NFs is 5157.1 mAmgPd−1, which is 6.0 times of Pd/C(JM) (866.7 mAmgPd−1). The residual current density value after 5000 s stability test is still 114.8 mAmgPd−1, which is 5.9 times of Pd/C(JM) (19.5 mAmgPd−1). The results showed that the nonmetal P doping was conducive to adjust the absorb energy of OHads and further facilitate the oxidation of COads. [Display omitted] •Nanoflower-like PdCuP catalysts were prepared to enhance ethanol electrooxidation.•Nonmetal P doping is helpful to adjust the electron structure and d-band center.•PdCuP NFs exhibited excellent activity and anti-poisoning ability for EOR.